2002
DOI: 10.1103/physreve.65.041707
|View full text |Cite
|
Sign up to set email alerts
|

Structure and elastic properties of smectic liquid crystalline elastomer films

Abstract: Mechanical measurements, x-ray investigations, and optical microscopy are employed to characterize the interplay of chemical composition, network topology, and elastic response of smectic liquid crystalline elastomers (LCEs) in various mesophases. Macroscopically ordered elastomer films of submicrometer thicknesses were prepared by cross linking freely suspended smectic polymer films. The cross-linked material preserves the mesomorphism and phase transitions of the precursor polymer. The elastic response of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 37 publications
2
41
2
Order By: Relevance
“…IV. However, it is consistent with the work of Stannarius et al, who performed mechanical experiments on Sm-A LCE balloons and found Mooney-Rivlin coefficients in the range 0 < c MR < 0.1 [11].…”
Section: Model Parameterssupporting
confidence: 92%
“…IV. However, it is consistent with the work of Stannarius et al, who performed mechanical experiments on Sm-A LCE balloons and found Mooney-Rivlin coefficients in the range 0 < c MR < 0.1 [11].…”
Section: Model Parameterssupporting
confidence: 92%
“…[6] Similar observations could be expected from homeotropically oriented thin elastomer films, produced by photo-crosslinking of a surface aligned S A polymer. However, neither spontaneous shape changes at the smectic-isotropic phase transformation nor a significant impact of the oriented layer structure on the rubber elastic modulus were observed for these materials, [12][13][14][15][16][17] which is in clear contrast to the S A LSCEs presented in this study. For elastomer E1 with the lowest crosslinking density the layer compression modulus B ¼ 1.1 Â 10 7 N Á m À2 is significantly larger than those observed for conventional low molar mass liquid crystals, where B is typically in the order of 1-5 Â 10 6 N Á m À2 for low measuring frequencies.…”
Section: Discussioncontrasting
confidence: 92%
“…[11][12][13][14] While for all S A LSCEs aligned by uniaxial stretching highly anisotropic mechanical properties and a macroscopic shape change at the LC-isotropic phase transformation have been reported, [4,5,8] no pronounced anisotropy of the elastic moduli and the macroscopic chain conformation was observed for homeotropic thin film elastomers. [12][13][14][15][16] This behaviour was attributed to the existence of microphase separated polysiloxane sublayers, which are characteristic for diluted polysiloxanes and might reduce the smectic layer compression modulus significantly. [17] In this paper we present the first experimental results on bulk S A LSCEs with homeotropic orientation, prepared by the anisotropic deswelling technique.…”
Section: Introductionmentioning
confidence: 99%
“…While the first deformation process causes layer reorientation above a characteristic threshold stress, the second process leaves the structure unmodified and indicates the in-plane fluidity of the smectic layers [4][5]. SmC elastomers, significant because of their optical and ferroelectric properties such as in the case of chiral molecules (SmC Ã phase) [6], have also been synthesized.…”
Section: Introductionmentioning
confidence: 99%